Heavy metals in sediments, mussels and oysters from Trinidad and Venezuela - Rojas de Astudillo, L. (2005)
The Gulf of Paria is bordered by both Trinidad and Venezuela, from which various metallic pollutants and other contaminants can originate. The Gulf is still a significant source of fish, crabs and shellfish for human consumption to both countries, where concerns over the quality of this marine environment have been long expressed but never properly addressed. In addition, the circulatory current patterns in the Gulf ensure that contaminants originating from either country are likely to affect both countries eventually. Heavy metals were determined in oysters (Crassostrea rhizophorae and C. virginica), green mussels (Perna viridis) and sediments from the Gulf of Paria. Samples were obtained at four sites in Trinidad and three sites in Venezuela in the Gulf of Paria, in addition to comparative samples collected from three sites on the north coast of Venezuela. Edible tissues of twelve shellfish from each location were blended and aliquots digested with concentrated nitric acid, for extraction of cadmium, chromium, copper, lead, nickel and zinc. The solutions were analysed by flame atomic absorption spectroscopy. Mercury was extracted with a mixture of nitric, hydrochloric and sulphuric acids and determined by cold vapour atomic absorption. Sediments were oven-dried at 60˚C, before being similarly extracted. Results showed that mercury in sediments at all sites in Trinidad and Venezuela exceeded NOAA and Canadian sediment quality guidelines, while cadmium, copper, nickel, lead and zinc also exceeded these guidelines at several sites. Heavy metal levels in oysters and green mussels varied widely with location. However, oysters from the Gulf of Paria contained significantly higher mean levels of cadmium, copper, nickel and zinc than those from the north coast of Venezuela, but this difference was not apparent in mussels. Cadmium, mercury and zinc in sediments were significantly correlated with those of mussels, but not of oysters, in which copper and zinc at several sites in the Gulf of Paria exceeded local maximum permissible levels (Cu = 20 μg g-1 wet wt; Zn = 50 μg g-1 wet wt) for human consumption. These findings indicate that while mussels may be better biological indicators of heavy metal pollution in sediments than oysters, the latter may provide copper and zinc contamination. Further research is needed to determine the most appropriate biological indicators of heavy metal and other pollutants in the local marine environment and to develop protocols for their use.